Multiplicity of positive radial solutions of a singular mean curvature equations in Minkowski space. (October 2016) - Pei, Minghe; Wang, Libo
Abstract: In this article, by using the Leggett–Williams' fixed point theorem, we prove the existence of at least three positive radial solutions of the singular Dirichlet problem for the prescribed mean curvature equation in Minkowski space div ( ∇ v 1 − | ∇ v | 2 ) + f ( | x |, v ) = 0 in Ω ; v = 0 on ∂ Ω, and the corresponding one-parameter problem. Here Ω is a unit ball in R N .,